Kindle Fire HDX for dummies - Muir, Nancy 1954- (For dummies, 2014)
Whether you want to use your new Kindle Fire HDX for work, play, or a little of both, you'll do it all with this easy-to-read reference. From navigating the touchscreen display and getting to know the built-in apps, to accessibility features and the X-Ray feature, this guide has everything you need to know.